Developing halal food supply chain integrity model in logistics industry: a conceptual review - Abdul Majid, Zawiah; Kamarulzaman, Nitty Hirawaty (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
Innovation is crucial for sustainability in Halal industry, in-line with the Malaysia’s aspiration to be the World Halal Hub. In Malaysia, Halal Industry Development Corporation Sdn. Bhd. (HDC) was formed in 2006 to spearhead and offer consultation pertaining to Halal enquiries and requirements. This conceptual review, Developing Halal Food Supply Chain Integrity Model in Logistics Industry could add value to Halal logistics players in managing he flow of Halal products and services towards innovative solutions. Halal food products are critically vulnerable to the hazards of food safety contamination and cross-contamination with non-halal materials or products. Pioneer attention of HDC that a Halal Standard on global logistics based on ‘farm-to-fork’ concept to ensure Halal Integrity is uphold throughout the food supply chain. Currently the study on Halal Integrity is limited therefore, developing Halal Food Supply Chain integrity model in the logistics industry is crucial not only could contribute advantages for Halal logistics players but to uphold the Halal integrity from origin to consumers in determining business sustainability.